Lean techniques for the improvement of patients’ flow in emergency department - Chan, HY (Second Affiliated Hospital of Zhejiang University School of Medicine, 2014)
BACKGROUND: Emergency departments (EDs) face problems with overcrowding, access block, cost containment, and increasing demand from patients. In order to resolve these problems, there is rising interest to an approach called “lean” management. This study aims to (1) evaluate the current patient flow in ED, (2) to identify and eliminate the non-valued added process, and (3) to modify the existing process. METHODS: It was a quantitative, pre- and post-lean design study with a series of lean management work implemented to improve the admission and blood result waiting time. These included structured re-design process, priority admission triage (PAT) program, enhanced communication with medical department, and use of new high sensitivity troponin-T (hsTnT) blood test. Triage waiting time, consultation waiting time, blood result time, admission waiting time, total processing time and ED length of stay were compared. RESULTS: Among all the processes carried out in ED, the most time consuming processes were to wait for an admission bed (38.24 minutes; SD 66.35) and blood testing result (mean 52.73 minutes, SD 24.03). The triage waiting time and end waiting time for consultation were significantly decreased. The admission waiting time of emergency medical ward (EMW) was significantly decreased from 54.76 minutes to 24.45 minutes after implementation of PAT program (P<0.05). CONCLUSION: The application of lean management can improve the patient flow in ED. Acquiescence to the principle of lean is crucial to enhance high quality emergency care and patient satisfaction.